Pola Konsumsi Media dan Perilaku Fujoshi dalam Mengapresiasi Boys Love Series Thailand (Studi Kasus di Kota Yogyakarta) - Puguh Priyo Cahyono (Commsphere: Jurnal Ilmu Komunikasi, 2025)
This study examines female fans' media consumption patterns and behavior, also known as fujoshi, in appreciating the Thai Boy's Love (BL) series in Yogyakarta City. Romantic relationships between men are depicted in the BL drama genre, which is highly desirable to female audiences. This study used a qualitative method with a case study approach to understand fujoshi's motivation, behavior, and consumption patterns toward BL. Data were collected through in-depth interviews, media content analysis, and direct observation of fujoshi community activities. The results show that fujoshi interpret BL as entertainment and a tool to explore and express views on identity, gender, and love. They actively shape new narratives and perceptions of LGBTQ+ issues through online and community interactions. This research reveals that fujoshi have different ways of receiving, interpreting, or rejecting messages from BL media using the Audience Reception Theory approach. In addition, this study shows that the popularity of BL contributes to discussions and possible social change while opening up space for greater tolerance and understanding of issues related to gender and sexual orientation in society. Kata Kunci: Boys love, Fujhosi Fans, LGBTQ+, Thai Series, Gender Identity